2012
DOI: 10.1016/j.expneurol.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Purkinje cell function prior to huntingtin accumulation and cell loss in an animal model of Huntington Disease

Abstract: Huntington Disease (HD) is a devastating neurological disorder characterized by progressive deterioration of psychiatric, motor, and cognitive function. Purkinje cells (PCs), the output neurons of the cerebellar cortex, have been found to be vulnerable in multiple CAG repeat disorders, but little is known about the involvement of PC dysfunction in HD. To investigate possible PC abnormalities, we performed quantitative real time PCR, western blot analysis, and immunohistochemistry experiments to explore the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
6
20
1
Order By: Relevance
“…Additionally, as evidenced by the PV staining, interneurons of the molecular layer were still present (arrows; Fig 2J). This staining pattern is strikingly similar to the one we previously observed in the R6/2 model (Dougherty, Reeves et al 2012) as well as to the pattern reported in a model of spinocerebellar ataxia-1 (Vig, Subramony et al 1998). Importantly, at this age, mutant htt inclusions were present within PCs of HdhQ200/Q200 mice (Fig 3).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, as evidenced by the PV staining, interneurons of the molecular layer were still present (arrows; Fig 2J). This staining pattern is strikingly similar to the one we previously observed in the R6/2 model (Dougherty, Reeves et al 2012) as well as to the pattern reported in a model of spinocerebellar ataxia-1 (Vig, Subramony et al 1998). Importantly, at this age, mutant htt inclusions were present within PCs of HdhQ200/Q200 mice (Fig 3).…”
Section: Resultssupporting
confidence: 90%
“…Given that a change in firing frequency was an early robust measure of PC dysfunction in the R6/2 mice (Dougherty, Reeves et al 2012), cell-attached loose patch electrophysiology was performed in 50 week old HdhQ200/Q200 and HdhQ200/+ mice (n=3–6 mice/group; 10–12 cells/group). Loose patch recordings revealed a significant reduction in spike frequency in the HdhQ200/Q200 mice as compared to age-matched WT controls (Fig 5; p<0.05), while there was no significant difference in firing rate in the HdhQ200/+ mice as compared to age-matched WT controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SHH and FGF8 were added after neuronal induction to generate these neurons. Cerebellar Purkinje neurons, which are known to have a crucial role in NPD 36 and HD 50,51 , appeared in our culture between 45–48 days, which is relatively longer and is a similar pattern as that observed in the developing cerebellum in vivo 29,30 . Thus, our method can rapidly generate subtype-specific or region-specific neurons compared to the other currently available neurodifferentiation methods 10,11,21,22 .…”
Section: Discussionsupporting
confidence: 69%
“…In the R6/2 model of HD, there is a striking reduction in Purkinje neuron firing frequency by postnatal day 28. It should be noted that there are no huntingtin inclusions in the Purkinje neurons until 12 weeks [73]. In the HdhQ200 model of HD, recordings were performed at a time where there was prominent Purkinje neuron loss, and loose patch electrophysiology of remaining Purkinje neurons identified a similar reduction in Purkinje neuron firing frequency in the HD mice compared with control littermates [74].…”
Section: Purkinje Neuron Dysfunction In Hd Modelsmentioning
confidence: 99%